Improving Hazard Map Comprehension for Protective Action Decision Making - Lindell, Michael K. (Frontiers in Computer Science, 2020)
A major challenge in the communication of spatial hazard information is the existence of substantial variation in people's ability to correctly infer the appropriate conclusions from hazard maps. Examination of the results from a variety of different types of hazard maps has identified patterns of erroneous as well as accurate processing of map information. In response, most hazard map studies have focused on the erroneous inferences and sought to develop displays that would cause hazard map viewers to make more accurate inferences about the hazard. This research has made some significant advances, but it has neglected the development and testing of spatial displays that can help people to make more timely and effective protective action decisions. This article concludes by summarizing the findings from hazard map research and recommending future research that will address these unresolved issues.